Reforestation, coffee and carbon in Sierra Piura, Peru: can carbon financing promote sustainable agriculture? - Amrein, Alexandra; Porras, Ina; Vorley, Bill (2015)
This report analyses a coffee and reforestation project in Peru led by a large coffee cooperative (Norandino) and a local NGO (Progreso). An ‘upstream–downstream’ approach links two groups of farmers in a climate-change mitigation and adaptation project: poor subsistence armers in the upper parts of Sierra Piura create carbon offsets through reforestation. These activities contribute to regeneration of the upper slopes of the watershed and reduce siltation for coffee producers located in the lower reaches of Sierra Piura. The coffee–carbon link is used to target carbon offset buyers through insetting. Carbon buyers offset their carbon emissions, while promoting resilience of coffee production at the base of their value chain. The report explores the challenges and opportunities associated with combining payments for ecosystem services with smallholder agriculture.